Exploring fungicides and sealants for management of Cytospora plurivora infections in western Colorado peach production systems. (August 2021) - Miller, S.T.; Sterle, D.; Minas, I.S.; Stewart, J.E.
Abstract: Cytospora plurivora, in western Colorado, is a limiting factor to peach production. The pathogen requires a wound, and entry points can be ubiquitous on peach trees depending on the season because of the need for tree cultural management (eg. dormant and/or summer pruning) and annual winter damage. Our study is focused on preventive control of the pathogen through wound protection. Fungicides and sealants were either evaluated in vitro, for antifungal activity, or selected from the present and previous trials to be evaluated in the field. Ten fungicide/sealant combinations were evaluated in the field for pathogen control during spring of 2018 and 2019 in western Colorado. Treatments included combinations of thiophanate-methyl, lime sulfur, VitiSeal (alone and in combination with other chemicals), with sealants (latex paint, paraffinic oil, and Nu-film 17). The fungicides/sealants that were most effective in reducing C. plurivora pathogen viability in branches and canker sizes was thiophanate-methyl alone, combined with VitiSeal, and combined with latex paint at 50 and 70% and VitiSeal combined with lime sulfur. The sealants Nu-film 17 and paraffinic oil, when combined with lime sulfur, were ineffective in all trials. Further, fungicides which showed evidence of efficacy in these studies and in previous studies were analyzed for their half maximum effective concentration rates (EC50 ) for an understanding of pathogen dose sensitivity. Highlights: Canker sizes and spore viability were reduced with thiophanate-methyl and VitiSeal. Latex with thiophanate-methyl and Lime sulfur with VitiSeal were effective. Sealants Nu-film 17 and paraffinic oil, with lime sulfur, were ineffective in trials. Fungicides were analyzed for EC50 for pathogen dose sensitivity. Latex was more effective with added fungicides.